Rating system for motor games based on age - Fernández-Revelles, A. B.; Moreno-Arrebola, R.; Espejo-Garcés, T.; Báez-Mirón, F.; Ramírez-Granizo, I. A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Introduction: Starting from the need to qualify motor games to guide children and adolescents in its use. Aim: Propose the bases for a motor games rating system starting from the videogame rating system. Methodology: Analysis of videogame rating systems. Results and Discussion: We have found different age rating systems for video games based on the descriptors: violence, sex and addictions that modify their impact depending on different modulators. They have many similarities and are widespread throughout the world. Conclusions: The bases for a proposal of a motor games rating system can be established starting from the systems of qualification of videogames, modifying qualification of age, descriptors and modulators in relation to the motor activity.